Understanding Student-Run Health Initiatives in the Context of Community-Based Services: A Concept Analysis and Proposed Definitions - Daniel A. Nagel; Taylor T. Naccarato; Mark T. Philip; Victoria K. Ploszay; Janice Winkler; Diana C. Sanchez-Ramirez; Jamie L. Penner (SAGE Publishing, 2022)
Background: Student-run health initiatives in the community setting have been utilized to provide practical experience for undergraduate students to develop professional competencies, gain exposure to diverse populations, and to engage in activities of social accountability. There is much literature on student-run health initiatives; however, there is no consensus on a definition of this concept or a comprehensive synthesis of the literature that describes student-run health initiatives offered by students in pre-licensure healthcare education programs. Purpose: To provide a concept analysis of, and propose a definition for, student-run health initiatives that provide community-based services for students during pre-licensure health discipline education. Methods: A systematic literature search and review process was used to identify and synthesize peer-reviewed articles from 7 academic databases covering a range of pre-licensure health disciplines and education. Walker and Avant's framework for concept analysis was used to guide exploration of attributes, antecedents and consequences of student-run initiatives, and to inform development of a definition for this concept. Results: The review yielded 222 articles for data extraction and represented 17 distinct pre-licensure health disciplines, 18 health-related disciplines, and a range of other baccalaureate and graduate programs. Our analysis revealed 16 definitions, 5 attributes, 6 antecedents, and consequences identified for student-run health initiatives. Attributes were Provision of Service, Service is Free, Target Clientele, Volunteerism, and Student Governance. Antecedents included Purpose/Rationale, Affiliation with Academic Unit, Location and Partnerships, Funding and Resources, Professional Oversight, and Preparation for Student Role. Consequences were improved access to services and outcomes for clients; competency development, personal gains and interprofessional learning for students; and positive outcomes for broader systems, such as decrease of service utilization and cost/benefit. Conclusions: There was no clear conceptual definition for student-run health initiatives, but many defining characteristics and well-described exemplars in the literature. Given the variations in purpose and scope of these initiatives, particularly to distinguish degree of students' roles in operations and the involvement of academic institutions, we propose 3 distinct conceptual definitions: student-run, student-led, and student-infused health initiatives.